Case Report: Calpainopathy Presenting After Bone Marrow Transplantation, With Studies of Donor Genetic Content in Various Tissue Types - Martens, Kristina; Leckie, Jamie; Fok, Daniel; Wells, Robyn A.; Chhibber, Sameer; Pfeffer, Gerald (Frontiers in Neurology, 2021)
We present a patient who had two allogeneic bone marrow transplantations for acute lymphocytic leukaemia. She developed slowly progressive limb-girdle weakness in the context of other symptoms of graft-versus-host disease (GVHD). Her myopathy symptoms had been initially attributed to GVHD, but when she progressed despite immunotherapy, genetic testing was requested. Initial testing was performed on a blood sample, identifying a variant of unknown significance in DMD. Subsequent testing of DNA from the patient’s muscle tissue identified two pathogenic variants in CAPN3, with absence of the DMD variant (this latter variant presumed to have been received from the donor). Allele-specific digital droplet qPCR permitted the quantification of the donor variant in various tissues from the patient (whole skin, isolated fibroblasts, whole blood, saliva, buccal cells, urine sediment, and two muscle biopsies taken at a two year interval). This report emphasizes that genetic disease should still be considered in the context of presumably acquired disease, and also demonstrates the extent of transdifferentiation of donor cells into other tissues.